Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-42
|View full text |Cite
|
Sign up to set email alerts
|

Restraining and encouraging the use of hand gestures: Effects on speech

Abstract: Previous studies have investigated the effects of the inability to make hand gestures on speakers' fluency; however, the question of whether encouraging speakers to gesture affects their fluency has received little attention. This study investigates the effect of restraining (Experiment 1) and encouraging (Experiment 2) hand gestures on the following correlates of speech: speech discourse length (number of words and discourse length in seconds), disfluencies (filled pauses, self-corrections, repetitions, inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
2
9
0
3
Order By: Relevance
“…The current line of research yields tangible implications for the continuing study of gesture-speech prosody. If the current exploratory findings can be replicated, gesture acoustics (Cravotta et al, 2018;Pouw, Harrison, et al, 2018b) will be shown to have affordances for real interpersonal embodied couplings. Understanding the social communicative significance these couplings would be our next research question.…”
Section: Brief Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The current line of research yields tangible implications for the continuing study of gesture-speech prosody. If the current exploratory findings can be replicated, gesture acoustics (Cravotta et al, 2018;Pouw, Harrison, et al, 2018b) will be shown to have affordances for real interpersonal embodied couplings. Understanding the social communicative significance these couplings would be our next research question.…”
Section: Brief Discussionmentioning
confidence: 82%
“…Namely, sudden increases in speech intensity and fundamental frequency are key properties that define the prosody of speech (Shattuck-Hufnagel & Ren, 2018;Wagner, Malisz, & Kopp, 2014), and spontaneous co-speech gestures are known to synchronize with such prosodic aspects of speech 6 (McClave, 1998;Rusiewicz & Esteve-Gibert, 2018). Scaling up to natural speech, other work has found that infants' babbling becomes more adult-like in voice quality when infants simultaneously and rhythmically move their arms (Ejiri & Masataka, 2001) and that encouraging gesture production during adults' speech production boosted maximum observed F0 and intensity of speech (Cravotta, Busà, & Prieto, 2018). Taken together, these findings are congruent with the idea that limb movement in itself is tied to changes in acoustic production, which provides a physical rudimentary basis for why gesture and speech tends to synchronize on the acoustic level.…”
Section: Figure 1 Example Movement Time Series and Concurrent Effects On Phonationmentioning
confidence: 99%
“…It appears that Rauscher et al (1996) did not, in fact, have any statistically significant results to support their influential claim that "speech with spatial content was less fluent when speakers could not gesture than when they could gesture" (ibid, p. 226). 1 Several studies in the last five decades, before and after Rauscher et al (1996), have also failed to find higher disfluency rates when speakers are prevented from gesturing than when they are allowed to gesture (Graham & Heywood, 1975;Rimé, Schiaratura, Hupet, & Ghysselinckx, 1984;Finlayson, Forrest, Lickley, & Beck, 2003;Hostetter, Alibali, & Kita, 2007;Hoetjes, Krahmer, & Swerts, 2014;Cravotta, Busà, & Prieto, 2018). Notably, none of the studies reporting null effects of gesture prevention distinguished between disfluencies during spatial and nonspatial speech; thus, arguably, these studies did not attempt to validate Rauscher et al's (1996) claim that gesture prevention selectively affects spatial speech.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects were exaggerated when participants were standing as opposed to sitting, suggesting a role for anticipatory muscle activations as these are more reactive when postural stability is low (Cordo & Nashner, 1982). As mentioned, changes in F0 have in fact been associated with gesture in natural contexts as well (Cravotta, Grazia, & Prieto, 2018;McClave, 1998;Wagner et al, 2014). Thus, it seems that this particular type of gesture-speech F0 and intensity synchrony (excluding possibly other types), may arise naturally from gesture-speech physics.…”
mentioning
confidence: 90%